Magneto-elastic coupling as a key to microstructural response of magnetic elastomers with flake-like particles. Issue 3 (23rd December 2021) - Dobroserdova, Alla; Schümann, Malte; Borin, Dmitry; Novak, Ekaterina; Odenbach, Stefan; Kantorovich, Sofia
Abstract : Modeling structural transitions in a magnetic elastomer filled with NdFeB flake-like particles caused by a strong magnetic field. Abstract : Using the combination of experiment and molecular dynamics simulations, we investigate structural transformations in magnetic elastomers with NdFeB flake-like particles, caused by applied moderate magnetic fields. We explain why and how those transformations depend on whether or not the samples are initially cured by a short-time exposure to a strong field. We find that in a cured sample, a moderate magnetic field leads mainly to in-place flake rotations that are fully reversed once the applied field is switched off. In contrast, in an initially non-cured sample the flakes perform both translation and rotations under the influence of a moderate applied field that lead to the formation of chain-like structures that remain such even if the field is switched off.